2016
DOI: 10.1007/s40204-016-0059-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative of fibroblast and osteoblast cells adhesion on surface modified nanofibrous substrates based on polycaprolactone

Abstract: One of the determinant factors for successful bioengineering is to achieve appropriate nano-topography and three-dimensional substrate. In this research, polycaprolactone (PCL) nano-fibrous mat with different roughness modified with O2 plasma was fabricated via electrospinning. The purpose of this study was to evaluate the effect of plasma modification along with surface nano-topography of mats on the quality of human fibroblast (HDFs) and osteoblast cells (OSTs)-substrate interaction. Surface properties were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…The smooth surface will have a smaller fiber diameter which would be suitable for the fibroblast cells to adhere and grow [18,31]. On other hand, Sharifi et al reported that surface modified polycaprolactone fibrous membrane with increased surface roughness also favors the improved adhesion and growth of fibroblast cells [33]. The influence of surface roughness on the cellular response is still unclear and the various physico-chemical properties of the manufactured composites might have a role in the cell adhesion behavior.…”
Section: Resultsmentioning
confidence: 99%
“…The smooth surface will have a smaller fiber diameter which would be suitable for the fibroblast cells to adhere and grow [18,31]. On other hand, Sharifi et al reported that surface modified polycaprolactone fibrous membrane with increased surface roughness also favors the improved adhesion and growth of fibroblast cells [33]. The influence of surface roughness on the cellular response is still unclear and the various physico-chemical properties of the manufactured composites might have a role in the cell adhesion behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Higher contact angle shows a low level of hydrophilicity of the substrates . Better cellular proliferation may be pertained to the hydrophilicity which promotes the rate of cellular proliferation …”
Section: Resultsmentioning
confidence: 99%
“…35 Better cellular proliferation may be pertained to the hydrophilicity which promotes the rate of cellular proliferation. 36 Observation of the WCA on the surface of core/shell nanofibers mats is useful, because of the difference in hydrophilicity of the PCL (hydrophobic) as core material and PVA-GEL (hydrophilic) as shell material. Figure 4 shows the WCA of crosslinked PCL/PVA-GEL core/shell nanofibers as well as PCL and crosslinked PVA-GEL nanofibers.…”
Section: The Shear Viscosity Of Emulsionmentioning
confidence: 99%
“…Cell behavior is complex phenomenon and it was influenced by various properties. The properties include fiber diameter, pore size, wettability, roughness, surface chemistry, surface energy, additives, and degradation [25,34,42,43,44,45,46,47,48]. It was reported that the smaller fiber diameter morphology will favors the enhanced cellular response [49].…”
Section: Resultsmentioning
confidence: 99%